MAXIM VIOLATIONS IN CROSS-CULTURAL COMMUNICATION: A PRAGMATIC STUDY OF RUMSPRINGA: AN AMISH IN BERLIN - Djawar, Asya Asyura; Wulandari, Julia (Universitas Islam Sumatera Utara (UISU), 2025)
This study shows on purpose violations of conversational maxims and their implied meanings in the Netflix film Rumspringa: An Amish in Berlin (2022) through a pragmatic and cross-cultural. The film shows Jacob, a young Amish man, going through Rumspringa in Berlin. The cultural differences Jacob sees show the various ways of communicating, values, and perspectives between the Amish way of life and modern city living. This study aims to identify the types of maxim violations and explain their pragmatic functions within the intercultural setting of the film. This research employs a descriptive qualitative method. In order to analyze data that were obtained from selected dialogues in the film using Grice’s Cooperative Principle framework (1975). The findings reveal that maxim of relevance, which is the sole maxim violated in the data, is employed as a strategy to communicate deeper meanings, express cultural identity, create humor, and subtly critique society. The study contributes to pragmatic and intercultural communication research by illustrating how media discourse reflects complex cultural negotiations through linguistic and multimodal implicature.